PÅ SIKKER GRUND: Genhusning efter tsunamien i Tamil Nadu - Hastrup, Frida (Tidsskriftet Antropologi, 2009)
This article explores the various meanings ascribed to destroyed, repaired and newly constructed houses in the South Indian fi shing village of Tharangambadi which was heavily affected by the tsunami disaster in December 2004. The article focuses on re-housing both as implemented by authorities and as understood by the survivors, thereby investigating divergent notions of danger and safety. The overall argument is that re-housing as a spatial practice is a much more comprehensive process than the mere shift of locality from a disaster-prone area to a safe area. By looking at practices of re-housing and the ways in which both old and new houses are engaged with and appropriated, it becomes clear that what is at stake for the survivors in Tharangambadi is a general attempt at establishing a sense of control over the physical surroundings, the trust in which was temporarily ruined by the tsunami. The article shows how in a disaster-affected region the sense of inhabiting a safe ground is dependent on something other and more than solid walls. Keywords: Catastrophy, security, hominess, materiality.